How Artificial Intelligence Transforms the Experience of Employees (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Artificial intelligence brings large markets, including advertising, tourism, finance, policy, workplace education. We probably associated with Chabot's job (defined as an automated, but personalized, a conversation between software and human users). We plan to use Chatbots in the workplace to assist us in pursuing a new career, addressing human resource questions, and also accepting coaching and mentoring after using them further in our personal lives. Since Chabot digitizes human resource programs, workers can access HR solutions from anywhere. HR artificial intelligence can result in a more streamlined, scalable and user-driven employee interface. To find the convergence between artificial intelligence and human resources, HR executives started using Chatbots in recruiting, staff service, staff production, and preparing to create greater value for the company. Indeed, Chabot's can be treated as the HR team's newest participant, capable of quickly finding solutions to commonly asked questions. Since we've grown accustomed to Chabot's in our everyday lives, we intend to use them at work. Artificial intelligence is changing how career applicants and workers interact. Five operational procedures are supposed to kick-start this new transformation when managers begin to implement artificial intelligence plans and roadmaps: 1. Experiment with different Chatbots to learn artificial intelligence. 2.Develop a joint strategy for HR, IT, Real Estate, Communitarians and Digital Transformation cross-functional partners; 3.Recognize how deployment can affect the technology roadmap; 4 Identify new job tasks that will make full usage of AI in HR; 5 Improve the understanding of artificial intelligence in the workplace by the HR team.